Enhancing Students’ Reading Comprehension through Gimkit at the 10th Grade Students of SMKN 1 Pangkalan Baru - Agustina, Mely (EEdJ: English Education Journal, 2025)
This study aimed to investigate whether there was a significant difference in students' reading comprehension between those taught using Gimkit and those who were not, as well as how does students' reading comprehension differ before and after implementing Gimkit at the 10th grade of SMKN 1 Pangkalan Baru. The research employed a quasi-experimental design with a pre-test and post-test control group involving 67 tenth-grade students of SMK Negeri 1 Pangkalan Baru. The participants were divided into two groups: 34 students in the experimental group and 33 in the control group. Both groups were given a pre-test and post-test focusing on short functional texts to measure their reading comprehension skill. The data were analyzed using t- tests in SPSS 26. The statistical analysis showed that the mean post-test score for the experimental group was 87.50, while the control group scored 59.85. The mean difference between the two groups was 27.653, with a standard error of 4.828. The Sig. (2-tailed) value was 0.000, and the t-obtained = 5.728, which was higher than the critical value of t-table = 2.00 at the 0.05 significance level with 65 degrees of freedom. Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. This means there was a significant difference in reading comprehension between students taught using Gimkit and those who were not. In conclusion, the use of Gimkit had a significant enhancement on the students' reading comprehension